Slope Stability Using Self-Drilling Anchor Rods - Bulko Roman; Mužík Juraj; Cigáň Filip (Civil and Environmental Engineering)
Efficient transport infrastructure is vital for economic competitiveness, yet landslides pose significant threats to roads, endangering safety and infrastructure. This article focuses on the rehabilitation of landslides using self-drilling anchors. Micropiles, which are reinforced drilled piles offer advantages in areas unsuitable for conventional foundation systems due to their adaptability to challenging terrain and minimal vibrations during installation. Our study focuses on a road site in the Bradl belt, characterized by significantly inclined terrain and medium plasticity clay soils. Using numerical modeling through AutoCad and Plaxis 2D, we evaluate the stability of the slope and the effectiveness of the micropile-reinforced concrete beam system. The φ-c reduction method was employed to assess the safety factor, showing that the spatial arrangement of micropiles enhances slope stability significantly. The results highlighted that a spatial orientation of micropiles improves the structural integrity and safely absorbs impacts, outperforming traditional arrangements. This study underscores the potential of micropiles for effectively addressing landslide threats, offering design, safety, and maintenance advantages.